Pelatihan Pembuatan Simulasi Jaringan Komputer Dengan Gns3 Dan Cisco Packet Tracer Kepada Para Guru SMKS Yapinuh Muara Gembong Kabupaten Bekasi Jawa Barat - Ali Idrus; Lipur Sugiyanta; Murien Nugraheni; F Fahrurrozi; Olifvia Afrillazhary; Zahwa Putri Rahmayani (Jurnal TUNAS, 2022)
In fulfilling the competence of Computer Network Engineering (TKJ) students in learning materials, it is not enough just to use theory but must be accompanied by practicum in the laboratory. Practicum aims to prove the theory learned in class. To support the practicum in the laboratory, hardware is needed such as a number of computers and computer network building components. Due to limited school resources due to the high cost of these devices, this is a separate problem that currently exists. The SMKS Yapinuh school laboratory for the TKJ study program is required to be active in developing a practicum model that can be a solution to the limitations of the availability of practicum equipment. To overcome these problems, namely by mastering computer network simulation software such as GNS3 and Cisco Packet Tracer which can fully represent the original network hardware functionality so that the limitations of providing computer network lab equipment can be overcome. Cisco packet tracer can display network simulation with topology display and hardware visualization so that it can be used as a computer network simulation and design tool. GNS3 allows detailed and complete network simulation, because it can run virtualization of the original operating system of network devices such as Mikrotik, Cisco and Juniper routers. So it's like being in a more real condition in configuring the router directly. This network simulator software training is expected to improve the understanding and skills of TKJ SMKS Yapinuh teachers in providing alternative learning facilities in the form of network simulations that can display hardware virtualization and computer operating systems and routers. so that the practicum process can be more interesting, interactive, shorten learning time and improve the quality of learning outcomes.